The Japanese-Specific out-of-Place Feeling Due to Clothing: A Combined Objective and Subjective Assessment Approach (Journal of Fiber Bioengineering and Informatics, 2024)
The feeling of being out-of-place from dressing differently from others is prevalent in Japanese individuals.However, previous studies have not objectively assessed this out-of-place feeling using physiologicalindices. Therefore, this study aimed to compare out-of-place feelings in Japanese individuals measuredusing questionnaires as subjective assessments and electroencephalography, R-R interval of heartbeats,and number of blinks as objective assessments. The results indicated that the participants felt out-of-place because of the differences in clothing and the recipient of the letter they wrote to as the task. Theout-of-place feeling had a significantly negative correlation with alpha waves and a significantly positivecorrelation with beta waves. The more the participants felt out-of-place, the more uncomfortable theywere when the collaborator entered or left the room wearing different clothes. The more their beta wavesactivated when they wrote a letter to their supervisor than when they wrote to children. The decrease inmiddle-alpha waves suggested that the participants were uncomfortable when they were the only peoplein a different outfit.
Keywords: Out-of-place; Japanese Female; EEG; Heartbeat R-R Interval; Questionnaire.